Far from Home: Profile of pro-IS Deportees’ Mobility throughout 2016-2020 and Prevention Strategy of Indonesian Government - Andi Raihanah Ashar; Curie Maharani (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2022)
Transnational terrorism has been a worldwide challenge, especially after the declaration of Islamic State (IS) that was based in Syria and Iraq in 2014. By 2017, most foreign terrorist fighters (FTFs) from Southeast Asia were Indonesian nationals, of almost 700 individuals. The actual number might be higher as some departed to Syria and other destination countries, like Afghanistan, the Philippines, and India, undetected. The research aimed to examine how Pro-IS terrorists exploit loopholes in border and immigration control to join IS abroad and the shortcoming in Indonesian government strategy to counter their mobility. The novelty of the research rested on its use of Supreme Court’s record of 38 Pro-IS deportees to build a dataset of their profile and travel history from 2016 to 2020. Profile of individual deportee was categorized into demography, affiliation, and funding. Travel history was mapped in accordance with the point of departure in Indonesia, transit country, final destination, and location where the arrest took place- which then led to deportation. The research finds that Indonesia needs improvement in human resources, law enforcement, immigration management, border control, as well as cross-border cooperation.